Dopant diffusion in sequentially doped Poly(3-hexylthiophene) studied by infrared and photoelectron spectroscopy - Reiser, Patrick; Sivanesan, Vipilan; Lovrinčić, Robert; Pucci, Annemarie; Beck, Sebastian (The journal of physical chemistry. C, Energy, materials, and catalysis, 2018)
The diffusivity of dopants in semiconducting polymers is of high interest as it enables methods of sequential doping but also affects device stability. In this study, we investigate the diffusion of a bulky sequentially deposited p-dopant in poly(3-hexylthiophene) (P3HT) thin films using nondestructive in situ infrared (IR) spectroscopy and photoelectron spectroscopy (PES). We probe dopant diffusion into the polymer film at varying coverage by differentially evaluating electron transfer in the bulk and at the surface. Thereby it is possible to determine dopant coverages at which both electron transfer and incorporation of dopants are saturated. By use of PES, neutral and charged dopants can be distinguished, revealing that charged dopants are less mobile in the diffusion process than neutral molecules. We further compare the diffusivity in semicrystalline and fully amorphous P3HT. We find that at high coverage semicrystalline P3HT seems to yield a higher capacity for dopants than fully amorphous P3HT. A temperature-dependent measurement of sequential doping shows directly that the incorporation of dopants is thermally activated and requires temperatures close to room temperature.
Gesehen am 24.01.2020